ANALISA NILAI-NILAI PATRIOTISME DALAM FILM TJOKROAMINOTO UNTUK MENUMBUHKAN SEMANGAT PATRIOTISME GENERASI MUDA - Suasridewi, Desak Gede (Journal of Urban Sociology, 2021)
In this Millenial era, especially the time where internet connection is limitless and everything is going digital, foreign values along with influences can easily breach into our society, notably in the mind of young generation. Those popular cultures and foreign shows doesn't just become a trend setter in this country, but also able to provide strong influences in people's social consciousness and cultural life, whether it's negative or positives. Strengthening and re-instating the patriotism along with nationalism values in Indonesia's current generation during this millenium era is very important and a must to grow the love and respect for our nation's own culture. Through film, it is hoped that the spirit and patriotism values among those younger generation can be built again. In this research, the object that the researcher's pick is a film called Tjokroaminoto. The problems of this research is on how those patriotism values are being represented in the movie. The method being used in this research is textual analysis which is part of cultural studies. Moreover, the textual analysis used in this research is semiotic. Results from this research showed that the movie Guru Bangsa Tjokroaminoto represented patriotism values through several forms, from dialogues, speeches and imaginary scenes. This study is expected to provide new insight into how patriotism values are represented in the film, as well as regenerate those values on the young generation.Â Keywords:Â  Guru Bangsa Tjokroaminoto, Media Film, Patriotism, SemioticÂ